Cell–cell fusion - Chen, Elizabeth H.; Grote, Eric; Mohler, William; Vignery, Agnès (FEBS letters, 2007)
Cell–cell fusion is a highly regulated and dramatic cellular event that is required for development and homeostasis. Fusion may also play a role in the development of cancer and in tissue repair by stem cells. While virus–cell fusion and the fusion of intracellular membranes have been the subject of intense investigation during the past decade, cell–cell fusion remains poorly understood. Given the importance of this cell-biological phenomenon, a number of investigators have begun analyses of the molecular mechanisms that mediate the specialized fusion events of a variety of cell types and species. We discuss recent genetic and biochemical studies that are beginning to yield exciting insights into the fusion mechanisms of Saccharomyces cerevisiae mating pairs, Caenorhabditis elegans epithelial cells and gametes, Drosophila melanogaster and mammalian myoblasts, and mammalian macrophages.